Microtubule Reorganization during Herpes Simplex Virus Type 1 Infection Facilitates the Nuclear Localization of VP22, a Major Virion Tegument Protein - Kotsakis, Anna (American Society for Microbiology, 2001)
Full-length VP22 is necessary for efficient spread of herpes simplex virus type 1 (HSV-1) from cell to cell during the course of productive infection. VP22 is a virion phosphoprotein, and its nuclear localization initiates between 5 and 7 h postinfection (hpi) during the course of synchronized infection. The goal of this study was to determine which features of HSV-1 infection function to regulate the translocation of VP22 into the nucleus. We report the following. (i) HSV-1(F)-induced microtubule rearrangement occurred in infected Vero cells by 13 hpi and was characterized by the loss of obvious microtubule organizing centers (MtOCs). Reformed MtOCs were detected at 25 hpi. (ii) VP22 was observed in the cytoplasm of cells prior to microtubule rearrangement and localized in the nucleus following the process. (iii) Stabilization of microtubules by the addition of taxol increased the accumulation of VP22 in the cytoplasm either during infection or in cells expressing VP22 in the absence of other viral proteins. (iv) While VP22 localized to the nuclei of cells treated with the microtubule depolymerizing agent nocodazole, either taxol or nocodazole treatment prevented optimal HSV-1(F) replication in Vero cells. (v) VP22 migration to the nucleus occurred in the presence of phosphonoacetic acid, indicating that viral DNA and true late protein synthesis were not required for its translocation. Based on these results, we conclude that (iv) microtubule reorganization during HSV-1 infection facilitates the nuclear localization of VP22.